Jus Postulandi : um instrumento restritivo de direitos ou de acesso no âmbito das varas do trabalho de São Luís/MA? - Marques, Igor Adriano Trinta (2022)
Among the facets necessary for access to the labor judiciary, there is the institute called jus postulandi. In this context, the main objective of this research is to analyze the nuances that exist in the specific case of the Labor Courts of the “Astolfo Serra” Forum in São Luís, belonging to the Regional Labor Court of the 16th Region, being necessary, therefore, to demonstrate the implications direct directives of the aforementioned institute for effective access to labor justice and all the existing fuss involving the theme, in addition to addressing critical biases and if really the institute in question is a benefit or a self-harm apart, if it should be extinguished or adapted to the new technologies of the electronic judicial process, of the hearings by videoconference, or still it appears as a skillful way to guarantee the right to the effective access of the hyposufficient parties to justice in the current and technological context. The applied methodology consists of hypothetical-deductive, exploratory in nature, from a qualitative approach, using bibliographic research techniques, doctrinal content analysis, jurisprudence and field research within the scope of the Labor Courts of São Luís/MA, as well as as involving the Public Defender's Office in the State of Maranhão. In the end, it was found that the jus postulandi, even though it needs convergent alternatives to reduce barriers to access to justice, is capable of implementing an effective fundamental right of access to justice and that the poor are entitled to the improvement of the aforementioned institute. based on the right to equality between the parties, which must be treated unequally to the extent of their inequalities, compensating for differences in a reasonable way and based on the primacy of public policies aimed at procedural and extrajudicial isonomy between the parties, as a massive investment in the expansion of the use of new digital technologies, access to information, insofar as access to justice itself differs from access to the judiciary. Therefore, material access to justice must be promoted to all and that in order to increase awareness, it is necessary to invest exponentially in citizenship, having as a guide education and information for the assimilation of new technologies, the possibility of the parties to learn right to have rights, the public authorities assuming a relevant role in the elaboration of the aforementioned public policies to alleviate these differences, not being able to forget about the monitoring and increase of popular participation, in accordance with the Federal Constitution and with a view to simplifying access, in order to promote the institute of jus postulandi.